Biomarkers in ovarian cancer: To be or not to be. (3rd December 2019) - Arend, Rebecca; Martinez, Alba; Szul, Tomasz; Birrer, Michael J.
Abstract : Biomarkers are becoming increasingly important in the treatment of epithelial ovarian cancer. Recent work from many laboratories has begun to provide clinically meaningful biomarkers. This review summarizes the state of the science regarding biomarkers for stratifying early‐stage patients into those who benefit from adjuvant treatment, primary debulking versus interval debulking, and specific targeted therapy. In addition, new molecular imaging technologies have been developed to allow the surgeon to resect subvisible tumor deposits. These efforts should increase clinical effectiveness while minimizing toxicities for patients. Abstract : Biomarkers for ovarian cancer have evolved into clinical significance. They are proposed to help in streamlining therapeutic interventions to improve clinical outcomes and the quality of life for all patients.